Body Mass Index Category Moderates the Relationship Between Depressive Symptoms and Diet Quality in Overweight and Obese Rural‐Dwelling Adults. Issue 4 (7th July 2017) - Abshire, Demetrius A.; Lennie, Terry A.; Chung, Misook L.; Biddle, Martha J.; Barbosa‐Leiker, Celestina; Moser, Debra K.
Abstract: Purpose: This study was conducted to (1) compare diet quality among depressed and nondepressed overweight and obese rural‐dwelling adults and (2) determine whether body mass index (BMI) category moderates the relationship between depressive symptoms and overall diet quality. Methods: Rural adults in Kentucky (n = 907) completed the 9‐item Patient Health Questionnaire (PHQ‐9) that assessed depressive symptoms and a food frequency questionnaire that generated 2005 Healthy Eating Index (HEI) scores. Participants were grouped into overweight (BMI 25‐29.9 kg/m 2 ) and obese (≥30 kg/m 2 ), and nondepressed (PHQ‐9 < 10) and depressed (PHQ‐9 ≥ 10) groups. Bootstrapped ANCOVAs were used to compare diet quality among the 4 groups. Ordinary least‐squares regression using PROCESS was used to determine whether BMI category (overweight vs obese) moderated the association between depressive symptoms and overall diet quality. Results: Overall diet quality was poorer in the obese depressed group than in the obese nondepressed group. Intake of fruit and dark green/orange vegetables and legumes was lower in the obese depressed group than in the overweight nondepressed group. Depressive symptoms predicted poor overall diet quality (B = −0.287, P < .001) and the relationship was moderated by BMI category (coefficient of BMI category * depressive symptom interaction term = 0.355, P < .049). A significant inverse relationship between depressive symptoms and overall diet quality was observed in the overweight group but not in the obese group. Conclusion: Components of diet quality vary according to BMI category and depressive symptom status. The relationship between depressive symptoms and diet quality is influenced by BMI category.